A graph based bundle adjustment for INS-camera calibration - Bender, D.; Schikora, M.; Sturm, J.; Cremers, D. (International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences - ISPRS Archives, 2013)
In this paper, we present a graph based approach for performing the system calibration of a sensor suite containing a fixed mounted camera and an inertial navigation system. The aim of the presented work is to obtain accurate direct georeferencing of camera images collected with small unmanned aerial systems. Prerequisite for using the pose measurements from the inertial navigation system as exterior orientation for the camera is the knowledge of the static offsets between these devices. Furthermore, the intrinsic parameters of the camera obtained in a laboratory tend to deviate slightly from the values during flights. This induces an in-flight calibration of the intrinsic camera parameters in addition to the mounting offsets between the two devices. The optimization of these values can be done by introducing them as parameters into a bundle adjustment process. We show how to solve this by exploiting a graph optimization framework, which is designed for the least square optimization of general error functions.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Aerial; Bundle adjustment; Calibration; Camera; Georeferencing; GPS/INS; Graph optimization; Non-metric